GEBELİK VE EPİLEPSİ: 44 OLGUNUN DEĞERLENDİRİLMESİ - MADAZLI, Rıza; ÖNCÜL, Mahmut; ULUDAĞ, Seyfettin; ALBAYRAK, Mustafa; EŞKAZAN, Esat; OCAK, Vildan (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Epilepsy is the most frequent neurologocical disorder after migraine during pregnancy. In this report, we aimed to determine the situation of epilepsy and pregnancy patients and share our clinical experiences in our country that prepregnancy consultation is insufficient. 44 epilepsy and pregnancy patients, whose gestational surveys were made at Cerrahpaşa Faculty of Medicine Department of Obstetric and Gynecology, were involved. The cases were evaluated by demographic characteristics like age, parity, gravida as well as how many years they had epilepsy, the last time of their seizure and the epileptic drugs they used before pregnancy. Results.- The mean delivery week was 39±0.7 weeks, and birth weight was 3291±474g. The mean epilepsy period was 11.7±9 years and epilepsy type was grand mal in 79.6%, petit mal in 4.5%, partial epilepsy in 15.9%. It was found that 24 of the 44 (54.5%) epilepsy and pregnancy patient had seizure during their follow-up. The seizures were more often seen during first 12 weeks and the patients that stopped taking antiepileptic drug treatment. 9 of the 11 patients (81.8%) that discontinued receiving drugs had an epileptic seizure. It was seen that only 22 epileptic pregnant patient had prepregnancy consultation. Conclusion.- The major goal in the follow-up of pregnancy and epilepsy patients should be taking seizures under control with minimum drugs. It can be possible to obtain good outcome almost like general population with appropriate approach and follow-up strategies.